AYURVEDIC APPROACH TOWARDS ANKYLOSING SPONDYLITIS- A CASE STUDY - Wilson, Nicy; MJ, Prashasth; Dr, Muralidhara (International Journal of Ayurveda and Pharma Research, 2018)
Ankylosing Spondylitis is a chronic, systemic, inflammatory disease that can cause the vertebrae to fuse in advanced stages. Ankylosing Spondylitis affects men more often than women. Signs and symptoms typically begin in early adulthood. This affects primarily the sacroiliac joints and spine. Certain peripheral joints and tendons can also be affected, and extra-articular manifestations may be present. The HLA B27 gene is commonly present, and there is a strong familial association. Due to the irregular dietary habits and Irregular activities like doing exercise soon after consuming food etc., leads to indigestion and formation of Amarasa. Through this article we are going to understand a case of Ankylosing Spondylitis in the line of Amavata through detailed history taking the course of the Samprapti is understood clearly and treated accordingly. A 37 years old male patient was presenting with the complaints of Low Back Pain associated with stiffness on low back region since 1 and 1/2 years and Neck pain associated with stiffness since 8 years. Though the Vyakta Lakshanas were at low back region, the initial Samprapti started from the Ama, Ajirna and so on. So in this case these factors are concentrated, assessed carefully and managed accordingly through various Abhyantara and Bahya Prayogas. Thereby following observations like reduction in Stiffness and pain, regularized and satisfactory bowel evacuation etc., were noted.